HERITAGIZATION IN UNIVERSITY HISTORICAL ARCHIVES AND LIBRARIES:THE CASE OF THE WORMALD COLLECTION OF THE UNIVERSITY OF TARAPACÁ - Moreno Falcón, Mónica; Ruz, Rodrigo Daniel (Revista de Historia Social y de las Mentalidades, 2020)
This article reflects on how conceptual changes in heritage processes have influenced policies of creation, preservation and use of historical university libraries in northern Chile from the end of the 20th century up to the present day. Taking the Wormald Cruz Patrimonial Collection of the University of Tarapacá as a case study, three key moments in its evolution are analyzed: the acquisition by the Junta de Adelanto de Arica in 1968, the purge and works developed during the dictatorship years and its recent enhancement as a heritage element. The review of the changes developed allows us to inquire into the relationship established between collection and local users and opens debate about the different ways of understanding documentary preservation.
Keywords: University Archives; Conservation; Heritagization; Subjectivity